Itraconazole and fluconazole-induced toxicity in rat hepatocytes: a comparativein vitro study - Somchit, N; Hassim, SM; Samsudin, SH (SAGE Publications, 2002)
This current study was to investigate the in vitrocytotoxicity of rat hepatocytes induced by the antifungal drugs, itraconazole and fluconazole. Both antifungal drugs caused dose-dependent cytotoxicity. In vitro incubation of hepatocytes with itraconazole revealed significantly higher lactate dehydrogenase (LDH) leakage when compared to fluconazole. Phenobarbital pretreated hepatocytes contained significantly higher total cytochrome P450 content than the control hepatocytes. P450 content was reduced approximately 30% for both types of hepatocytes after 6 hours incubation. Interestingly, cytotoxicity of itraconazole was reduced significantly by phenobarbital pretreatment. Phenobarbital did not have any effect on the cytotoxicity induced by fluconazole. These results demonstrate the in vitro toxicity of hepatocytes induced by itraconazole and fluconazole that were expressed in a dose and time-dependent manner. Phenobarbital plays a role in the cytoprotection of hepatocytes to itraconazole-induced but not fluconazole-induced cytotoxicity in vitro.